18 F‐flortaucipir tau positron emission tomography distinguishes established progressive supranuclear palsy from controls and Parkinson disease: A multicenter study - Schonhaut, Daniel R.; McMillan, Corey T.; Spina, Salvatore; Dickerson, Bradford C.; Siderowf, Andrew; Devous, Michael D.; Tsai, Richard; Winer, Joseph; Russell, David S.; Litvan, Irene; Roberson, Erik D.; Seeley, William W.; et al. (Annals of neurology, 2017)
F-flortaucipir (formerly F-AV1451 or F-T807) binds to neurofibrillary tangles in Alzheimer disease, but tissue studies assessing binding to tau aggregates in progressive supranuclear palsy (PSP) have yielded mixed results. We compared in vivo F-flortaucipir uptake in patients meeting clinical research criteria for PSP (n = 33) to normal controls (n = 46) and patients meeting criteria for Parkinson disease (PD; n = 26). Participants underwent magnetic resonance imaging and positron emission tomography for amyloid-β ( C-PiB or F-florbetapir) and tau ( F-flortaucipir). F-flortaucipir standardized uptake value ratios were calculated (t = 80-100 minutes, cerebellum gray matter reference). Voxelwise and region-of-interest group comparisons were performed in template space, with receiver operating characteristic curve analyses to assess single-subject discrimination. Qualitative comparisons with postmortem tau are reported in 1 patient who died 9 months after F-flortaucipir. Clinical PSP patients showed bilaterally elevated F-flortaucipir uptake in globus pallidus, putamen, subthalamic nucleus, midbrain, and dentate nucleus relative to controls and PD patients (voxelwise p < 0.05 family wise error corrected). Globus pallidus binding best distinguished PSP patients from controls and PD (area under the curve [AUC] = 0.872 vs controls, AUC = 0.893 vs PD). PSP clinical severity did not correlate with F-flortaucipir in any region. A patient with clinical PSP and pathological diagnosis of corticobasal degeneration had severe tau pathology in PSP-related brain structures with good correspondence between in vivo F-flortaucipir and postmortem tau neuropathology. F-flortaucipir uptake was elevated in PSP versus controls and PD patients in a pattern consistent with the expected distribution of tau pathology. Ann Neurol 2017;82:622-634.